African genesis : perspectives on hominin evolution - Reynolds, Sally C.; Gallagher, Andrew, 1975- (Cambridge studies in biological and evolutionary anthropology, 2012)
Reviews key themes and developments in palaeoanthropology, exploring their impact on our understanding of human origins in Africa.